Distributional Effects of Environmental Taxes on Transportation. Evidence from Engel Curves in the United States - Erling Røed Larsen (Statistics Norway, Research Department, 2005)
Indirect taxes on transportation activities that pollute can correct externalities and close the gaps between private and social costs. However, policy makers often find such Pigou taxes difficult to implement because of political resistance due to possibly adverse affects on equity. For this reason it is important to assess the distributional aspects of environmental levies. This article estimates properties of the demand for transportation in parametric and non-parametric analyses of Consumer Expenditure Surveys for the United States, 2000, and finds patterns in the resulting set of Engel curves. Private transportation using air flights and new automobiles have Engel elasticities above unity while public transportation via mass transit has Engel elasticity below unity. The findings can be interpreted in an important way since they show that a differentiated scheme of environmental taxes on transportation may function progressively. A Pigou scheme with larger taxes on modes of transportation that pollute more appears to coincide with larger levies on luxury modes preferred by richer households.
Keywords: D12; D31; H23; R41; 330; consumption patterns; double dividend; Engel curves; environmental levies; equity; externality; indirect taxation; Pigou correction; redistribution; transportation; travel